PENGARUH HARGA DAN PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI PADA PT. GLOBAL HEALTH SCREENING CENTRE MEDAN - Clarrissa Winata (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the influence of price and service quality on customer loyalty, with customer satisfaction as a moderating variable at PT. Global Health Screening Centre Medan. The research method used is a quantitative approach, with a sample of 40 customers of PT. Global Health Screening Centre. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results indicate that price and service quality significantly affect customer loyalty. Moreover, customer satisfaction is proven to moderate the relationship between price and loyalty, as well as between service quality and customer loyalty.